Theory and methods of cultivating English Language competence among future bachelors of computer science in the context of distance learning - Derbak, Olha; Vynnyk, Olha; Bodnar, Iryna; Godis, Yulia; Solohub, Larysa (Perspectivas em Diálogo: Revista de Educação e Sociedade, 2026)
The relevance of this study is underscored by the imperative to cultivate professional English competence among IT students against the backdrop of education digitalization and market globalization. This article elucidates the findings from an investigation into the efficacy of distance learning methodologies in fostering English language competence among students specializing in "Computer Science" across Ukraine, Poland, and Kazakhstan. The purpose of the study was to determine the dynamics of various components of foreign language competence under the influence of targeted pedagogical interventions. The methodological framework included a pedagogical experiment involving both control and experimental groups (CG and EG), standardized testing, a paired t-test, an online questionnaire, and a content analysis of open-ended responses. The results showed statistically significant changes within the experimental groups (p < 0.05), with an improvement ranging from +21 to +23 points across all components. The beneficial effects of scaffolded materials, authentic communicative tasks, and intercultural interaction were demonstrated. The scientific novelty of this research lies in the synthesis of a component-based approach to evaluating language competence with the intercultural context inherent in distance learning. Prospects for further research are related to the adaptation of the proposed model to other fields of study and the examination of its implications within professional environments